2021
DOI: 10.3389/fnagi.2021.758895
|View full text |Cite
|
Sign up to set email alerts
|

Flavones 7,8-DHF, Quercetin, and Apigenin Against Tau Toxicity via Activation of TRKB Signaling in ΔK280 TauRD-DsRed SH-SY5Y Cells

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease with memory loss and cognitive decline. Neurofibrillary tangles (NFTs) formed by hyperphosphorylated Tau protein are one of the pathological hallmarks of several neurodegenerative diseases including AD. Heat shock protein family B (small) member 1 (HSPB1) is a molecular chaperone that promotes the correct folding of other proteins in response to environmental stress. Nuclear factor erythroid 2-like 2 (NRF2), a redox-regulated transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Of noted, quercetin showed no protective effect in their apoptotic assay. By fluorescence quenching analysis, we confirmed the binding between quercetin and extracellular domain of TRKB, and the highest binding affinity (5.3 ± 1.9 nM) echoes the highest interacting docking score (49.77) with TRKB receptor (Chiang et al, 2021). In the pharmacokinetic study in healthy volunteers, the maximum blood concentration of oral administration with quercetin at the dose of 100 mg is 7.65 μM (Graefe et al, 2001).…”
Section: Discussionmentioning
confidence: 57%
“…Of noted, quercetin showed no protective effect in their apoptotic assay. By fluorescence quenching analysis, we confirmed the binding between quercetin and extracellular domain of TRKB, and the highest binding affinity (5.3 ± 1.9 nM) echoes the highest interacting docking score (49.77) with TRKB receptor (Chiang et al, 2021). In the pharmacokinetic study in healthy volunteers, the maximum blood concentration of oral administration with quercetin at the dose of 100 mg is 7.65 μM (Graefe et al, 2001).…”
Section: Discussionmentioning
confidence: 57%
“…Similar results were seen with apigenin and 7,8-dihydroxyflavone (7,8-DHF). Chiang et al (2021) proposed that the activation of the Nrf2 pathway may be partly mediated by the activation of tropomyosin receptor kinase B (TRKB), a brain-derived neurotrophic factor (BDNF) receptor, which upregulates Akt activation, an activator of Nrf2, and thus decreases the mutant Tau protein aggregation [ 32 ]. Another assay in SH-SY5Y cells stressed by high glucose concentration showed that quercetin improved cell viability through an upregulation of glyoxalase 1 activity.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…This finding indicated that quercetin can be used as a potential therapeutic drug in the management of AD by regulating the α7nAChR/Nrf2/HO-1 signaling pathway. In addition, quercetin treatment can reduce tau aggregation and protected cells against tau neurotoxicity by mediating the expression of heat shock protein family B member 1 (HSPB1), NRF2, and tropomyosin-related kinase B (TRKB) (Chiang et al, 2021). Previous studies revealed that the levels of NRF2 can be upregulated by AKT serine/threonine kinase 1 (AKT), one of the downstream proteins activated by TRKB (Yoo et al, 2017).…”
Section: Flavonoidsmentioning
confidence: 99%